Improve the Teaching Competencies on Linguistic-Communicative Area of Future Teachers on Early Childhood Education by Using Service-learning (Revista Lusófona de Educação, 2021)
The pre-service training of infant teachers aims to awaken in students a commitment to their profession and educational improvement. It attempts to initiate them in rigorous processes of thinking about their competencies and how to regulate and improve them. We present the partial results of a mixed methodological research project1 that analyses how students of the Bachelor’s Degree in Early Childhood Education are impacted by an innovation that uses service-learning (SL) to teach students linguistic communicative teaching competencies while they work with their lecturers in schools in underprivileged contexts that are promoting early multilingualism. We analyze how the students’ perception of their competencies evolves and compare it with the lecturers’ assessment. We observe that actions (SL) that involve designing, carrying out, and evaluating real interventions in schools bring satisfaction because they combine theory and practice, and students need to be able to cope with important professionalcontent. The experience also increases students’ perception of their own self-efficacy, places the work done by the students and lecturers in the context of investigative professional communities, and leads to learning processes aligned with the linguistic-communicative teaching competencies that are required in multilingual and inclusive schools.Keywords: pre-service teacher education; early childhood education; service-learning; linguistic-communicative competencies; relationship between theory and practice.